The role of JNK phosphorylation as a molecular target to enhance adenovirus replication, oncolysis and cancer therapeutic efficacy - Wechman, Stephen L. (Cancer Biol Ther, 2018)
Oncolytic adenoviruses (Ads) are cancer selective tumoricidal agents; however their mechanism of Ad-mediated cancer cell lysis, or oncolysis, remains undefined. This report focuses upon the autophagy mediator c-JUN n-terminal kinase (JNK) and its effects upon Ad oncolysis and replication. Previously, E1b-deleted Ads have been used to treat several hundred cancer patients with limited clinical efficacy. We hypothesize that by studying the potential interactions between E1b and JNK, mechanisms to improve oncolytic Ad design and cancer therapeutic efficacy may be elucidated. To test this hypothesis, E1b was selectively deleted from the Ad genome. These studies indicated that Ads encoding E1b induced JNK phosphorylation predominately occurred via E1b-19K. The expression of another crucial Ad gene E1a was then overexpressed by the CMV promoter via the replication competent Ad vector Adhz69; these data indicated that E1A also induced JNK phosphorylation. To assess the effects of host cell JNK expression upon Ad oncolysis and replication, siRNA targeting JNK1 and JNK2 (JNK1/2) were utilized. The oncolysis and replication of the E1b-19K wild-type Ads Ad5 and Adhz63 were significantly attenuated following JNK1/2 siRNA transfection. However the oncolytic effects and replication of the E1b-19K deleted Ad Adhz60 were not altered by JNK1/2 siRNA transfection, further implicating the crucial role of E1b-19K for Ad oncolysis and replication via JNK phosphorylation. This study has demonstrated for the first time that JNK is an intriguing molecular marker associated with enhanced Ad virotherapy efficacy, influencing future Ad vector design.